SPATHIAN (LOWER TRIASSIC) CONODONTS FROM THE TIROLITES CASSIANUS BEDS IN PALEOTETHYS-ISSUED NORTH DOBROGEA OROGEN (ROMANIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
The paper documents a conodont fauna from Lower Triassic deposits of Paleotethys-issued North Dobrogea Orogen. The studied strata exposed in the Tulcea Veche Quarry are characterized by the presence of diversified molluscs, including the ammonoid Tirolites cassianus (Quenstedt) and the bivalve Crittendenia decidens (Bittner). The site also represents the type locality of the coelacanth fish Dobrogeria aegyssensis Cavin & Grădinaru. The recovered conodont fauna is marked by Icriospathodus crassatus (Orchard), Neospathodus robustispinus Zhao & Orchard, Novispathodus abruptus (Orchard), Nv. brochus (Orchard), Nv. aff. brochus (Orchard), Tr. ex gr. homeri (Bender), Tr. hungaricus (Kozur & Mostler), Tr. ex gr. hungaricus (Kozur & Mostler), Tr. symmetricus (Orchard), Tr. aff. symmetricus (Orchard), and Triassospathodus sp. that is correlated with the Tr. symmetricus Zone.
Keywords: Biostratigraphy; Olenekian; Tulcea Veche Quarry; Romania